The WUJUD BANGUNAN ARSITEKTUR BALE SAKENEM: (STUDI KASUS: DESA WISATA PENGLIPURAN, KECAMATAN KUBU, KABUPATEN BANGLI, BALI) - Winardi, Kenny (Jurnal Teknik Sipil dan Arsitektur, 2024)
Bale Sakenem is one of the many buildings of traditional Balinese architecture which function to accommodate traditional ceremonial activities. Its specific function is to prepare and carry out religious ceremonies for Hindus. Basically, this architectural building has a wall structure that has six pillars or six saka, therefore this architectural bulding is named Bale Sakenem. The contruction ans structure of this building uses wood materials. Bale Sakenem is owned by all residents’ houses in the Panglipuran Tourism Village, Kubu District, Bangli Regency, Bali. Basically, it still maintains itsshape, structure, contruction and ornaments, but there are changes that have occuredin the materials. This reseach uses a qualitative descriptive method with an ase study approach. Research data was obtained from direct observation in the Panglipuran Tourism Village. The research conclusion shows that the materials used in the Bale Sakenem architectural buildings still use wood materials with changes in wood types nowadays.